2004
DOI: 10.1209/epl/i2004-10276-4
|View full text |Cite
|
Sign up to set email alerts
|

Domain growth in random magnets

Abstract: PACS. 75.40-Dynamical properties, dynamical scaling, numerical simulation. PACS. 05.50.+q -Lattice theory and statistics (Ising, Potts, etc.). PACS. 75.10.Nr -Spin-glass and other random models.Abstract. -We study the kinetics of domain growth in ferromagnets with random exchange interactions. We present detailed Monte Carlo results for the nonconserved random-bond Ising model, which are consistent with power-law growth with a variable exponent. These results are interpreted in the context of disorder barriers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
130
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(159 citation statements)
references
References 26 publications
25
130
4
Order By: Relevance
“…This has been corroborated by numerical simulations [2] as well as analytical results in exactly solvable limits [1,3]. As shown by Paul et al [4], a power law domain growth is also observed for the present disordered system, which suggests to plot, here also, C(t, t w ) as a function of t/t w : this is depicted in Fig. 3a.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This has been corroborated by numerical simulations [2] as well as analytical results in exactly solvable limits [1,3]. As shown by Paul et al [4], a power law domain growth is also observed for the present disordered system, which suggests to plot, here also, C(t, t w ) as a function of t/t w : this is depicted in Fig. 3a.…”
supporting
confidence: 87%
“…A recent numerical study of the relaxational dynamics in two-dimensional random magnets [4] found evidence for a power law growth L(t) ∝ t 1/z of the aforementioned length scale L(t). The dynamical exponent z turned out to depend both on temperature T and disorder strength and to behave as z ∝ 1/T at low temperatures T .…”
Section: Pacs Numbersmentioning
confidence: 99%
“…One issue that has attracted much attention recently concerns ordering processes, relaxation phenomena, and the formation of domains in disordered systems. Examples include vortex lines in disordered type-II superconductors, [1][2][3][4][5] polymers in random media, [6][7][8][9] coarsening of disordered magnets, [10][11][12][13][14][15] and slow dynamics in spin glasses. 13,16,17 Our understanding of relaxation phenomena and aging processes in nonfrustrated systems with slow dynamics has greatly progressed during the last decade, mainly through the systematic study of critical and coarsening ferromagnets ͑see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Monte Carlo simulations of various disordered ferromagnetic Ising models [10][11][12][13][14][15] found for the dynamical correlation length L͑t͒ a power-law increase, L͑t͒ϳt 1/z , with a nonuniversal dynamical exponent z that depends on temperature and on the nature of the disorder. This behavior can be explained by assuming that the energy barriers grow logarithmically with L. 10,11 As a consequence, it follows that the dynamical exponent z should be inversely proportional to the temperature: z ϳ 1 / T. Whereas this temperature dependence has been observed in the CardyOstlund model, 19 a careful study 14 has revealed that in the random-bond Ising model the temperature dependence of the dynamical exponent is more complicated. This fact points to the existence of conceptual problems in the approach of Paul et al 10,11 In addition, an algebraic growth law is in strong contrast to the classical theory of activated dynamics that, under the assumption of energy barriers growing as a power of L, predicts a slow logarithmic increase 20 in this length: L ϳ͑ln t͒ 1/ , with the barrier exponent Ͼ 0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation